Myocarditis in childhood report of 67 patients (Annals of Medical Research, 2022)
Aim: The aim of this study is to evaluate the clinical findings, sociodemographic characteristics and follow -up of the myocarditis cases and to investigate factors affecting the mortality.Materials and Methods: Patients who diagnosed myocarditis from January 2009 to December 2017 were included in this study. Sex, date of admission, age at the time of admission, presence of previous infection, physical examination findings, serum cardiac biomarkers, whole blood count, C reactive protein and viral serology results, electrocardiographic findings, telecardiography and echocardiographical findings and the medical records about complications and mortality during follow-up were analysed. Statistical analyzes performed with IBM SPSS 22.0. Pearson chi-square and continuity corrected chi-square tests were used. Numerical data were summarized with median, minimum and maximum values. Univariate Kaplan - Meier and Cox regression analyzes were used in comparisons. The significance level was accepted as 0.05 in all tests.Results: From January 2007 to December 2017, 67 patients with myocarditis were retrospectively analyzed. 31 (46.2%) patients were recovered. 21 patients (31.3%) developed dilate cardiomyopathy. Six patients were died in acute phase. 7 of 21 patients with dilate cardiomyopathy were died at follow-up period. Nine patients were referred to a cardiovascular surgery center for VAD, ECMO or cardiac transplantation. Among them seven patients were died under ECMO. 2 patients were implanted VAD.Conclusion: Myocarditis is an inflammatory disease of the myocardium. Diagnosis of myocarditis may be difficult to subtle clinical findings. The clinical picture may be varying from a mild subclinical period to congestive heart failure. The prognosis varies from recovery to complicated chronic disease and death. In our study, increased cardiothoracic index and pulmonary congestion findings in telecardography, increased serum myoglobin level and decreased echocardiographic shortening fraction were factors associated with increased mortality. The using the cardiac support devices in patients with myocarditis may decrease mortality.
Keywords: Dilated cardiomyopathy; heart failure; myocarditis